The population of mentally disadvantaged in Nigeria: health and development programme (1995)
The paper considered the fact that the actual population of the mentally disadvantaged in Nigeria needs to be known, so that its economic importance on the overall development of the country can be assessed. By projection, and using comparative assessment methods from Nigeria and other countries, the writers estimated the population of the mentally disadvantaged in Nigeria to be 1.77million, and submit that this has grave consequences on the health programme and the general development of the nation. The writers contend that at present, Nigeria does not have adequate health facilities and programmes for its mentally disadvantaged citizens. However, attempts at provision of facilities can be found based in the homes of the mentally disadvantaged, in educational institutions, hospitals and at governmental level. The productivity of the mentally disadvantaged is very low, and to provide food, water, shelter, and other amenities to almost 2 million mentally disadvantaged, in a depressed economy will have a tremendously negative effect on Nigeria's development. The paper concluded that the situation can however be made better and the mentally disadvantaged can contribute thier own quota to the per-capita earnings for the nation. This could be achieved by making them productive through adequate training and provision of educative health programmes that have legislative backing. More researches and the use of therapeutic methods could help the mentally disadvantaged to learn and cope with some life situations. |Urban designs should accommodate the mentally disadvantaged and the soical integration strategies should be more humane and all embracing.